2016
DOI: 10.4014/jmb.1508.08024
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Antiviral Activity of Cinnamomum cassia and Its Nanoparticles Against H7N3 Influenza A Virus

Abstract: Nanoparticles have wide-scale applications in various areas, including medicine, chemistry, electronics, and energy generation. Several physical, biological, and chemical methods have been used for synthesis of silver nanoparticles. Green synthesis of silver nanoparticles using plants provide advantages over other methods as it is easy, efficient, and eco-friendly. Nanoparticles have been extensively studied as potential antimicrobials to target pathogenic and multidrug-resistant microorganisms. Their applicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
73
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(76 citation statements)
references
References 58 publications
0
73
0
3
Order By: Relevance
“…Therefore, these cytotoxicity results could have been due to this precursor rather than the particles themselves. Low cytotoxicity is one of the most important requirements for any potential antiviral agent; Fatima et al described the non-toxicity (CC 50 > 500 µg/mL) of synthesized green nanoparticles and their precursors tested in the same way by the MTT assay on Vero cells [20]. Cagno et al also reported the lack of significant toxicity at similar concentrations (CC 50 ≥ 100-300 µg/mL) of gold NPs coated with undecanesulfonic acid (MUS)-containing ligands and their pre-MUS ligand [21].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, these cytotoxicity results could have been due to this precursor rather than the particles themselves. Low cytotoxicity is one of the most important requirements for any potential antiviral agent; Fatima et al described the non-toxicity (CC 50 > 500 µg/mL) of synthesized green nanoparticles and their precursors tested in the same way by the MTT assay on Vero cells [20]. Cagno et al also reported the lack of significant toxicity at similar concentrations (CC 50 ≥ 100-300 µg/mL) of gold NPs coated with undecanesulfonic acid (MUS)-containing ligands and their pre-MUS ligand [21].…”
Section: Discussionmentioning
confidence: 99%
“…One of the important areas in the field of medicine is to evaluate the effects of nanoparticles for the treatment of viral, bacterial, fungal, and parasitic infection with particular focus on the multidrug-resistant pathogens. In one study, the nanoparticle from cinnamon has been found effective as an antiviral agent against the H7N3 influenza A virus in the Vero cells without any toxic effects on these cells [10]. Another important area is the prevention of cancers and many other diseases which are associated with the increased production of free radicles.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to mention that despite a wide variety of studies existing in the literature, antimicrobial activity has generally been evaluated in the same microorganisms even though there is a large amount of bacteria, fungi and viruses of clinical importance that could be studied. Also, when existing studies are analyzed (Table 1), most suggest that biosynthesized silver nanoparticles are biocompatible and may have therapeutic use potential in humans; however, if we review the studies summarized in Table 1 very few carry out biocompatibility tests in normal cells [8,10,14,15,18,26,27]. These tests provide crucial information on the ranges of safety and cytotoxicity of the biosynthetized nanoparticles, information that result fundamental to can be designed future experiments with biomedical applications in preclinical and clinical models.…”
Section: Antimicrobial Activitymentioning
confidence: 99%
“…As shown in Table 1 [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27], the antimicrobial effect of the green silver nanoparticles, mainly their antibacterial [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] and antifungal action [10,[12][13][14]17,18,[23][24][25], has been widely reported. It is important to mention that despite a wide variety of studies existing in the literature, antimicrobial activity has generally been evaluated in the same microorganisms even though there is a large amount of bacteria, fungi and viruses of clinical importance that could be studied.…”
Section: Antimicrobial Activitymentioning
confidence: 99%
See 1 more Smart Citation